Acceptance and closeness as opposed to rejection and neglect as emotional aspects of a parent/child relation, and their influence on young person's mental health and his social competence - Slavković Ana R. (University of Kragujevac - Faculty of Pedagogy, Užice, 2020)
This article considers how supporters of different directions in psychology explain the importance of closeness and acceptance by parents for the proper development of the child (supporters of attachment theory, classical psychoanalysts, NEO-psychoanalysts, behaviourists). All theorists agree that the love that a child receives from a parent is the basic pillar of child's mental health, some emphasizing the importance of the first years of life (classical psychoanalysts), some childhood up to the age of ten (supporters of attachment theory), and some a relationship between a parent and a child throughout adolescence (ego and self-psychologists). Some theorists emphasize the importance of forming positive internal introjects, ie "working models" of oneself and others, which serve to predict interpersonal interactions and determine a basically positive image of oneself and the world, while others (behavioural theorists) emphasize the importance of parent-child intimacy, with the aim to facilitate the identification process and to internalize the socially desirable characteristics of parents and other role models. The paper also analyzes the way parents manifest acceptance or rejection of the child, the consequences that such actions leave on the child (according to the findings of researchers), as well as the importance of closeness with a same-sex parent or parent of the opposite sex for the child's emotional well-being. In the second part of the paper, we consider the reasons for the rejection of the child by the parents and highlight the importance of parental characteristics, relationship between parents, characteristics of the child, as well as some factors that have nothing to do with the child's identity. We believe that the greatest influence on the rejection of the child has the pathology of the parent himself, which leads to deep internal disintegration and to the projecting of unacceptable parts of the self on a child, so that the parent sees the child as bad, wrong or incompetent.